2023
DOI: 10.1186/s12879-023-08298-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary SARS-CoV-2 infection in patients with immune-mediated inflammatory diseases: long-term humoral immune responses and effects on disease activity

Abstract: Background Patients with immune-mediated inflammatory diseases (IMIDs) on immunosuppressants (ISPs) may have impaired long-term humoral immune responses and increased disease activity after SARS-CoV-2 infection. We aimed to investigate long-term humoral immune responses against SARS-CoV-2 and increased disease activity after a primary SARS-CoV-2 infection in unvaccinated IMID patients on ISPs. Methods IMID patients on active treatment with ISPs and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Indeed, in this study, anti-SARS-CoV-2 antibodies were only assessed at the end of the follow-up for all patients, and in patients who were seropositive at the time of their last infusion, anti-SARS-CoV-2 antibody assays were retrospectively performed at each of their visit in order to determine the time of seroconversion. Thus, we may have underestimated the number of pauci-symptomatic infections if they were contracted early during the follow-up, particularly for patients treated with anti-TNF, that can attenuate seroprevalence as suggested in some studies ( 43 , 44 ), even though another study recently showed that patients with IBD previously infected with COVID-19 have similar quantitative antibody response as healthy controls previously infected with COVID-19 ( 45 ). The parallel can be drawn with the response to the vaccination because the antibody levels after vaccination have been shown to be lower with anti-TNF agents than with other treatments, studied in this prospective case-control study (483 cases for 121 controls) between May and November 2021, in which the antibody level measured between 53 and 92 days after the second vaccination dose was lower under infliximab (geometric mean ratio 0.12, 95% CI 0.08-0.17; p<0.0001), compared to thiopurines (0.89, 0.64-1.24; p=0.50), ustekinumab (0.69, 0.41-1.19; p=0.18), or vedolizumab (1.16, 0.74-1.83; p=0.51) ( 32 ).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, in this study, anti-SARS-CoV-2 antibodies were only assessed at the end of the follow-up for all patients, and in patients who were seropositive at the time of their last infusion, anti-SARS-CoV-2 antibody assays were retrospectively performed at each of their visit in order to determine the time of seroconversion. Thus, we may have underestimated the number of pauci-symptomatic infections if they were contracted early during the follow-up, particularly for patients treated with anti-TNF, that can attenuate seroprevalence as suggested in some studies ( 43 , 44 ), even though another study recently showed that patients with IBD previously infected with COVID-19 have similar quantitative antibody response as healthy controls previously infected with COVID-19 ( 45 ). The parallel can be drawn with the response to the vaccination because the antibody levels after vaccination have been shown to be lower with anti-TNF agents than with other treatments, studied in this prospective case-control study (483 cases for 121 controls) between May and November 2021, in which the antibody level measured between 53 and 92 days after the second vaccination dose was lower under infliximab (geometric mean ratio 0.12, 95% CI 0.08-0.17; p<0.0001), compared to thiopurines (0.89, 0.64-1.24; p=0.50), ustekinumab (0.69, 0.41-1.19; p=0.18), or vedolizumab (1.16, 0.74-1.83; p=0.51) ( 32 ).…”
Section: Discussionmentioning
confidence: 96%